Assessment of sanitation service gap in urban slums for tackling COVID-19 - Nishat Shermin; Nafiz Rahaman (Journal of Urban Management, 2021)
Coronavirus disease 2019 (COVID-19), caused by Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), has been declared as a global pandemic by the World Health Organization (WHO). As the disease is highly infectious, the Global South countries are in a vulnerable situation with high urban population density and lack of Water, Sanitation, and Hygiene (WASH) services. The situation for the urban slum dwellers and low-income group clusters are becoming worse. Lack of health and sanitation service availability has already been an issue for them before the beginning of the pandemic. So, it is predictable that adopting this massive global pandemic is a critical challenge for them. This paper assesses the sanitation service gap in urban slums, which has become a severe challenge to tackle due to COVID-19. The study areas of this research are the Ranarmath slum and the Khema slum of Khulna city, Bangladesh. The SERVQUAL model has been used to identify the quality of sanitation service available in these informal residential settlements. The interpretation of questionnaire survey data from the two slums reveals that one slum lacks Assurance and Empathy, where the other slum lacks Tangibility and Responsiveness. However, the Tangibility, Reliability, and Responsiveness condition of both slums are flawed with the lack of latrine functionalities and services from concerned authorities. The incompatibility of the condition has been identified by evaluating the WHO's different sanitation management policy for COVID-19. The research concludes that sanitation services like handwashing facilities and water supply availability in the latrine directly related to COVID-19 prevention are indigent for these slums.
Keywords: 710; Sanitation service; COVID-19; SERVQUAL; Public health